Zur Nachfeldbesetzung im Deutschen - MIKOŁAJCZYK, Beata (Wydawnictwo Naukowe UAM, 1997)
The matter of the study was Nachfeld in the german language. I intended that the word-order in this fiels is not only an optional phenomenon but also conditioned by grammar. That is why, it ought to be refered not only to the stylistics as it used to.